(untitled) (Global Journal of Human-Social Science, 2023)
With this study we intend to demonstrate that the management of water resources in the south of Angola between the Republics of Angola and Namibia is carried out mainly at the state level Even the 1888 agreement between the Portuguese and Germans the basis for the agreement to delimit the southern border of Angola between the Portuguese and South Africans 22 June 1926 was related to the need to manage water resources The use of the waters of the cross-border Cunene river with a length of more than a thousand kilometers of which around 70 in Angolan territory and the remainder on the border line with the Republic of Namibia its diversion to the Etocha lagoon was the condition unique way to alleviate aridity in Damaral ndia a sine quo non condition for the implementation of this delimitation These agreements remain in force to this day complemented by initiatives after independence with a view to making better use of the Calueque and Ruacan dams on the Cunene river aiming to improve the lives of the populations of both countries both in terms of water supply and of electrical energy